2018
DOI: 10.1002/jcb.28243
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of Coleus forskohlii relieves cough and asthma symptoms via modulating inflammation and the extracellular matrix

Abstract: Asthma is characterized by airway inflammatory infiltration, which leads to airway remodeling and airway hyperreactivity. Coleus forskohlii (CFK) has been used to treat asthma, however, the mechanism involved is not clear. To explore the antiasthma mechanism of extracts of Coleus forskohlii (ECFK), guinea pigs were administered with a spray of phosphoric acid histamine, and rats were sensitized with ovalbumin (OVA). Hematoxylin and eosin staining (H&E) were used to evaluate pathological changes in lung tissue.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…In the brain, MMP-9 not only acts as an inflammatory mediator involved in the development of inflammation reactions, but also as a proteolytic enzyme involved in BBB degradation [8,42]. Studies to date have demonstrated that excessive MMP-9 in the brain may aggravate inflammatory reactions and allows for inflammation infiltration into the brain parenchyma since it disrupts the integrity of BBB by attacking the extracellular matrix, basal lamina and TJs in the BBB [10,43,44]. Moreover, MMP-9 is also involved in the cleavage of IL-1β from its precursor to mature form [9].…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, MMP-9 not only acts as an inflammatory mediator involved in the development of inflammation reactions, but also as a proteolytic enzyme involved in BBB degradation [8,42]. Studies to date have demonstrated that excessive MMP-9 in the brain may aggravate inflammatory reactions and allows for inflammation infiltration into the brain parenchyma since it disrupts the integrity of BBB by attacking the extracellular matrix, basal lamina and TJs in the BBB [10,43,44]. Moreover, MMP-9 is also involved in the cleavage of IL-1β from its precursor to mature form [9].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, forskolin has been proven to have immunomodulatory effects in an experimental model of auto-immune encephalomyelitis through interruption of macrophage/microglia activation, and infiltration and production of IFN-γ by CD4 T cells [ 159 ]. Furthermore, there was evidence for the bronchodilator effects of forskolin attributed to suppressing generation of various inflammatory cytokines and chemokines; NFkB‐p65, IL‐4, interleukin-5 (IL‐5), IL‐17 and ICAM‐1 together with downregulation expression of MMP‐9, and tissue inhibitor of metalloproteinase-1 (TIMP‐1) in lung tissue by stabilizing the extracellular matrix [ 160 ]. In addition, forskolin has been shown to possess anti-platelet activity mediated by elevating levels of platelet cAMP [ 161 ].…”
Section: Drugs That Might Affect the Cytokines Storm In Covid-19mentioning
confidence: 99%
“…In Ayurvedic practice, Anu Taila is used for Nasya processes (nasal drops) to reduce inflammation in nasal passage and respiratory tract. The polyherbal components of Anu Taila, Aegle marmelos ( Nicolis et al, 2009 ; Pynam and Dharmesh, 2018 ; Rajaram et al, 2018 ), Asparagus racemosus ( Gautam et al, 2009 ; Kanwar and Bhutani, 2010 ; Tiwari et al, 2017 ), Aquilaria agallocha ( Yadav et al, 2013b ), Cedrus deodara ( Gupta et al, 2011 ), Cinnamomum verum ( Hagenlocher et al, 2013 ), Coleus vettiveroides ( Ma et al, 2019 ), Cyperus esculentus ( Krichene et al, 2016 ), Cyperus rotundus ( Kamala et al, 2018 ), Desmodium gangeticum ( Yadav et al, 2013a ), Elettaria cardamomum ( Majdalawieh and Carr, 2010 ), Embelia ribes ( Shirole et al, 2015 ), Glycyrrhiza glabra ( Lee et al, 2019 ), Nelumbo mucifera ( Zhao et al, 2010 ), Ocimum sanctum ( Choudhury et al, 2014 ), and Pogostemon cablin ( Yang et al, 2018 ) have anti-inflammatory potential and can ameliorate pro-inflammatory cytokines such as IL-1β, TNF-α, IFN-γ, IP-10, MCP-1, IL-4, and IL-8.…”
Section: Introductionmentioning
confidence: 99%